Lithium ion battery composite solid polymer electrolyte material and preparation method thereof

By preparing new lithium arylsulfonimide salt and MIL-88B (Fe) nanoparticles in lithium-ion batteries, combined with PEO matrix, the safety problems of liquid electrolytes in lithium-ion batteries and the performance limitations of polyethylene oxide solid electrolytes are solved, and high-performance composite solid electrolyte materials are achieved, improving the safety and service life of the battery.

CN119864499APending Publication Date: 2025-04-22GUIZHOU NORMAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411866602.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

Safety issues such as leakage, volatility, poor thermal stability and internal short circuit in existing lithium-ion batteries, and the high crystallinity, low ionic conductivity and poor interfacial compatibility of polyethylene oxide solid polymer electrolytes at room temperature limit their practical application.

Method used

The novel lithium arylsulfonimide salt (Li-FBTFSI) was prepared by sulfonylation and ion exchange reaction, and MIL-88B(Fe) nanoparticles were synthesized by solvothermal method and added to the PEO matrix to prepare high-performance PEO-based composite solid polymer electrolyte material.

Benefits of technology

It significantly improves the solid electrolyte performance of lithium-ion batteries, enhances the migration rate of lithium ions, inhibits the growth of lithium dendrites, improves electrochemical performance and safety, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119864499A_ABST
    Figure CN119864499A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium ion battery composite solid polymer electrolyte material and a preparation method thereof, novel aryl sulfonimide lithium salt (Li-FBTFSI) is prepared through sulfonylation and ion exchange reaction, MIL-88B (Fe) nanoparticles are synthesized by using terephthalic acid as a ligand and ferric trichloride hexahydrate as a metal salt through a solvothermal method, and the MIL-88B (Fe) composite solid polymer electrolyte material is prepared. And then adding the MIL-88B (Fe) nano-particles into a PEO matrix by taking a novel aryl sulfonyl imide lithium salt (Li-FBTFSI) as a lithium salt, so as to obtain the PEO-based composite solid polymer electrolyte material with high performance. The prepared solid electrolyte material improves the performance of the solid electrolyte, does not have the problems of electrolyte leakage, high-temperature volatilization, nonflammability and the like, has very high safety, does not cause the problems of low reversible capacity and short cycle life of the battery, and is suitable for large-scale popularization and application. The polymer solid-state lithium ion battery can be prepared into a safe and stable polymer solid-state lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a novel lithium ion battery composite solid polymer electrolyte material and a preparation method and application thereof, belonging to the technical field of lithium ion batteries. Background Art

[0002] Lithium-ion batteries (LIBs) have become an irreplaceable and excellent energy storage device with their advantages such as high output voltage, long service life and high energy density. However, safety issues such as leakage, volatilization, poor thermal stability and internal short circuit of liquid organic electrolytes in lithium-ion batteries have brought great safety problems to the application of lithium-ion batteries. The preferred method to solve these problems is to replace traditional liquid electrolytes with solid electrolytes, which can effectively alleviate the growth of lithium dendrites and avoid the effects caused by internal short circuits and liquid leakage.

[0003] Many studies have reported ion-conductive solid polymer electrolytes (SPEs) based on polyethylene oxide (PEO), polyacrylonitrile (PAN), polyvinylidene fluoride (PVDF), etc. Polyethylene oxide has attracted much attention due to its ability to dissolve various lithium salts by interacting with cations through ether oxygen bonds. Polyethylene oxide (PEO)-based solid polymer electrolytes (SPEs) are considered to be one of the most promising electrolytes in the next generation of solid-state lithium metal batteries. They are composed of a polymer matrix and dissolved lithium salts and have the characteristics of good film-forming properties and high processing flexibility. However, due to the high crystallinity of PEO at room temperature, the SPEs have a high crystallinity at room temperature, low ionic conductivity at room temperature, and poor interfacial compatibility with lithium metal. The low ionic conductivity and poor interfacial compatibility hinder the practical application of polyethylene oxide-based SPEs at room temperature. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a lithium ion battery composite solid polymer electrolyte material and a preparation method and application thereof, thereby solving the problems existing in the above-mentioned prior art.

[0005] In order to solve the above technical problems, the technical solution of the present invention is as follows:

[0006] A lithium-ion battery composite solid polymer electrolyte material is prepared by sulfonylation and ion exchange reaction to prepare a new type of arylsulfonyl imide lithium salt (Li-FBTFSI), and terephthalic acid is used as a ligand and hexahydrate ferric chloride is used as a metal salt. MIL-88B (Fe) nanoparticles are synthesized by a solvent thermal method. Then, the new type of arylsulfonyl imide lithium salt (Li-FBTFSI) is used as a lithium salt, and the MIL-88B (Fe) nanoparticles are added to a PEO matrix to obtain a high-performance PEO-based composite solid polymer electrolyte material.

[0007] A method for preparing a lithium-ion battery composite solid polymer electrolyte material comprises the following steps:

[0008] (1) Synthesis of novel arylsulfonyl imide lithium salt (Li-FBTFSI): 3.10 g 4-fluorobenzenesulfonyl chloride, 2.38 g trifluoromethanesulfonamide, 0.51 g 4-dimethylaminopyridine and 60 mL ultra-dry acetonitrile were added to a round-bottom flask, and 4.5 g anhydrous potassium carbonate was added after ultrasonic dissolution. The mixture was stirred at room temperature under nitrogen protection for 48 h to carry out ion exchange reaction.

[0009] After the reaction is completed, the supernatant is taken by centrifugation, the solvent is removed by rotary evaporation, 30 mL of acetone is added to dissolve, the solution is dropped into 300 mL of dichloromethane, the supernatant is poured off after ultrasonication, the precipitate is taken by centrifugation, and dried at 60°C; the dried solid is dissolved in 20 mL of acetone, allowed to stand overnight, the supernatant is taken by centrifugation, the supernatant is taken by rotary evaporation, the precipitate is taken by centrifugation, recrystallized with acetone and dichloromethane, the precipitate is taken by centrifugation, dried at 60°C, and impurities are removed to obtain a white solid (4-fluorobenzenesulfonyl)(trifluoromethylsulfonyl)imide potassium (K-FBTFSI);

[0010] Then, an equimolar amount of KFBTFSI and LiClO4 were dissolved in ultra-dry acetonitrile, and stirred for 24 hours at room temperature under nitrogen protection to perform an ion exchange reaction; after the reaction, the clear liquid was centrifuged and dried, 60 mL of acetonitrile was added, and the clear liquid was centrifuged and dried after ultrasonic dissolution, and dichloromethane was added and ultrasonicated until the solution became uniform milky white, and the solution was placed in a desiccator and allowed to stand overnight, and the precipitate was centrifuged and dried in vacuo at 60° C. to obtain a white solid (4-fluorobenzenesulfonyl) (trifluoromethylsulfonyl) imide lithium (Li-FBTFSI);

[0011] (2) Synthesis of MIL-88B (Fe) nanoparticles: First, 0.675 g of ferric chloride hexahydrate and 0.166 g of terephthalic acid were weighed into a small glass bottle, 15 mL of ultra-dry N, N-dimethylacetamide was added, and after ultrasonic dissolution, the mixture was transferred to a 20 mL reactor and reacted at 110 °C for 24 h.

[0012] After the reaction is completed, the mixture is cooled to room temperature and centrifuged to obtain a solid product, which is washed with ultra-dry N,N-dimethylacetamide and anhydrous ethanol until the solution is clear, and the precipitate is centrifuged and dried in vacuum at 60°C.

[0013] Finally, the product was extracted with anhydrous methanol at 100 °C for 24 h, dried under vacuum at 60 °C, and ground into powder with a size between 150 and 500 nm to obtain MIL-88B (Fe) nanoparticles;

[0014] Preparation of MIL-88B(Fe) doped PEO-based composite solid polymer electrolyte membrane: According to the EO / Li +=20:1, weigh the corresponding mass of PEO and Li-FBTFSI and dissolve them in ultra-dry acetonitrile, add MIL-88B(Fe) to the mixed solution according to 10wt% of the mass of PEO, stir at 60°C in a nitrogen atmosphere for 24h to obtain a uniform viscous liquid, then pour the solution into a polytetrafluoroethylene mold, place it in a dryer equipped with molecular sieves, and allow most of the solvent to evaporate at room temperature; finally, vacuum dry at 60°C for 24h to remove excess organic solvent, transfer to a glove box for cooling, and obtain MIL-88B(Fe)-doped PEO-based CPEs.

[0015] Application of MIL-88B(Fe) nanoparticles in the preparation of polymer solid-state lithium-ion batteries.

[0016] Beneficial effects: Compared with the prior art, the present invention provides a lithium-ion battery composite solid polymer electrolyte material and its preparation method and application. First, a new type of lithium salt (Li-FBTFSI) is used, which is an aromatic sulfonyl imide lithium salt substituted with a strong electron-withdrawing group (-F). Then, MIL-88B (Fe) nanoparticles are synthesized by a solvothermal method. On the one hand, Fe 3+ It can combine with the anions of lithium salts to promote the dissociation of lithium salts and release more Li + On the other hand, Fe 3+ It can also combine with the unsaturated groups in PEO to promote Li + The transmission of Li on the PEO chain segment improves + The continuous pores inside can promote the migration of lithium ions and destroy the crystallinity of PEO, effectively alleviating the growth of lithium dendrites, thereby improving the performance of the solid electrolyte, so that it can be prepared as a safe and stable polymer solid-state lithium-ion battery. The solid electrolyte material prepared by the present invention is a solid electrolyte, which does not have the problems of electrolyte leakage, high-temperature volatilization, etc., and is non-flammable, so it has very high safety.

[0017] The solid electrolyte in the present invention does not react with the electrode material during the cycle process, so the battery capacity is not easy to decline; the solid electrolyte in the present invention is stable and does not decompose under high potential, so it will not cause the problems of low reversible capacity and short cycle life of the battery, so that the composite solid polymer electrolyte material of the present invention can be prepared into a safe and stable polymer solid-state lithium-ion battery.

[0018] The present invention aims at the problems of PEO-based SPEs in the prior art, and solves the problems by modifying the polymer matrix and designing new lithium salts. The applicant has found through research that adding inorganic fillers to modify the polymer matrix of SPEs and developing composite solid polymer electrolytes (CPEs) with both high ionic conductivity and mechanical strength is a good solution. Introducing nanofillers into SPEs can effectively improve ionic conductivity and interface performance. Metal organic frameworks (MOFs) are a new type of porous filler with a three-dimensional structure. It combines the rigidity of inorganic fillers and the flexibility of organic materials and is widely used in composite solid polymer electrolytes. When MOFs are doped as fillers, they can reduce the glass transition temperature (T g ) to improve the ionic conductivity of the polymer, increase segmental motion, and increase Li + The highly ordered pore structure and abundant open metal sites (OMSs) of MOFs materials help promote the dissociation of Li + dissociation and transport of Li, increasing the contact area between the electrode and the electrolyte, while inhibiting the occurrence of side reactions and promoting Li + It is uniformly deposited on the surface of lithium metal and inhibits the growth of lithium dendrites.

[0019] At the same time, lithium salts, as an important component of electrolytes, have always attracted the attention of researchers. In past studies, people have invested a lot of research efforts in the synthesis and characterization of borates, imidazolates, triazoles and other lithium salts. Only a few researchers have studied aromatic functionalized fluorosulfonyl imide type lithium salts, but most of their efforts are to study polymer-based electrolytes to form single-ion conductive polymers, functionalizing styrene with fluorosulfonyl imide groups as monomers to form a lithium salt covalently linked to the polymer backbone, and there is less research on aromatic functionalized substituents.

[0020] Therefore, the present invention provides a lithium ion battery composite solid polymer electrolyte material and its preparation method and application. A novel arylsulfonyl imide lithium salt (Li-FBTFSI) substituted with a strong electron-withdrawing group (-F) is designed and prepared by sulfonylation and ion exchange reaction. At the same time, terephthalic acid is used as a ligand and hexahydrate ferric chloride is used as a metal salt to synthesize MIL-88B (Fe) nanoparticles by a solvothermal method. With Li-FBTFSI as a lithium salt, the EO / Li + =20, the activated MIL-88B(Fe) was added to the PEO matrix at 5wt%, 10wt% and 15wt% of the PEO mass to prepare PEO-based CPEs containing different proportions of MIL-88B(Fe), which significantly improved the electrochemical properties of PEO-based CPEs.

[0021] MIL-88B(Fe) contains a large amount of Lewis acid Fe3+ as metal active sites, which combines with the anion FBTFSI-, which is beneficial to the dissociation of Li+; at the same time, the porous structure of MIL-88B(Fe) enables Li+ to transfer in the pores, providing more Li+ transmission channels and optimizing the ion transmission path.

[0022] The results show that 10%-MIL-88B CPE has a higher ionic conductivity (60℃, 1.35×10 -4 S cm -1 ) and a broadened electrochemical stability window (~5.18 V). The lithium symmetric battery assembled with 10%-MIL-88B CPE can be -2 It can run stably for 2000h at a current density of 0.2C without short circuit, effectively inhibiting the growth of lithium dendrites. At the same time, the CPE also has excellent performance in battery performance. At 60℃, its first discharge capacity is 141.1mA·h / g at 0.2C, and the maximum discharge capacity reaches 150.2mA·h / g in the fourth cycle. After 100 cycles, it still has a high discharge capacity of 139.9mA·h / g, a capacity retention rate of 99.1%, and a coulombic efficiency of nearly 100%. Based on this, we believe that 10%-MIL-88B CPE has good electrochemical properties, and it also shows that the addition of MIL-88B (Fe) helps to inhibit the growth of lithium dendrites, improve the interface compatibility between the polymer electrolyte and the lithium metal anode, and effectively improve the electrochemical performance of the polymer electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 is the synthesis route of Li-FBTFSI of the present invention;

[0024] Figure 2 It is the synthesis route of MIL-88B (Fe) of the present invention;

[0025] Figure 3 The structure of MIL-88B(Fe) of the present invention, viewed along the a-axis (left) and c-axis (middle), and a μ3-oxygen-bridged trimer unit consisting of iron octahedron and terephthalate linker (right);

[0026] Figure 4 is the XRD spectrum of (a) MIL-88B(Fe) of the present invention;

[0027] Figure 5 is a SEM image of MIL-88B (Fe) of the present invention;

[0028] Figure 6are photographs of 5%, 10% and 15%-MIL-88B CPEs of the present invention in flat and bent states;

[0029] Figure 7 is a SEM image of 10%-MIL-88B CPE of the present invention;

[0030] Figure 8 is the EDS mapping diagram of C, O and Fe elements on the surface of 10%-MIL-88B CPE of the present invention;

[0031] Fig. 9 The cyclic voltammetry curves of (a) Li / without-MIL / LFP and (b) Li / 10%-MIL-88B / LFP of the present invention are shown;

[0032] Fig.10 The long cycle performance of Li / CPEs / LFP at (a) 0.2C and (b) 0.5C of the present invention;

[0033] Fig.11 is the rate performance of (a) Li / CPEs / LFP of the present invention;

[0034] Fig.12 The charge and discharge curves of (b) Li / 10%-MIL-88B / LFP at different rates of the present invention;

[0035] Fig.13 The AC impedance diagram of (a) Li / 10%-MIL-88B / Li at different storage times of the present invention;

[0036] Fig.14 is the interface impedance change curve of the Li / CPEs / Li symmetric battery of the present invention (b);

[0037] Fig.15 It is the cycle curve of the Li / CPEs / Li symmetric battery of the present invention at 0.1 mA cm-2. DETAILED DESCRIPTION

[0038] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation mode, structure, characteristics and effects of the present invention are described in detail below in combination with the accompanying drawings and preferred embodiments.

[0039] The invention discloses a lithium ion battery composite solid polymer electrolyte material. The material is prepared by sulfonylation and ion exchange reaction to prepare a novel aryl sulfonyl imide lithium salt (Li-FBTFSI), and terephthalic acid is used as a ligand and ferric chloride hexahydrate is used as a metal salt to synthesize MIL-88B (Fe) nanoparticles by a solvent thermal method. Then, the novel aryl sulfonyl imide lithium salt (Li-FBTFSI) is used as a lithium salt, and the MIL-88B (Fe) nanoparticles are added into a PEO matrix to obtain a high-performance PEO-based composite solid polymer electrolyte material.

[0040] The present invention provides a method for preparing a composite solid polymer electrolyte material for a lithium ion battery, comprising the following steps:

[0041] 1. Synthesis of lithium (4-fluorobenzenesulfonyl)(trifluoromethylsulfonyl)imide (Li-FBTFSI) and lithium (4-cyanobenzenesulfonyl)(trifluoromethylsulfonyl)imide (LiCBTFSI)

[0042] Synthesis route such as Figure 1 As shown, 3.10g 4-fluorobenzenesulfonyl chloride (15.93mmol), 2.38g trifluoromethanesulfonamide (15.96mmol), 0.51g 4-dimethylaminopyridine (4.18mmol) and 60mL ultra-dry acetonitrile were added to a round-bottom flask, and 4.5g anhydrous potassium carbonate was added after ultrasonic dissolution, and stirred for 48h at room temperature and under nitrogen protection. After the reaction was completed, the supernatant was centrifuged, the solvent was removed by rotary evaporation, 30mL acetone was added to dissolve, and the solution was dropped into 300mL dichloromethane, and the supernatant was poured off after ultrasonic standing, and the precipitate was centrifuged and dried at 60°C. The dried solid was dissolved in 20mL acetone, stood overnight, centrifuged to take the supernatant, rotary evaporated, recrystallized with acetone and dichloromethane, centrifuged to take the precipitate, and dried at 60°C to obtain a white solid (4-fluorobenzenesulfonyl) (trifluoromethylsulfonyl) imide potassium (K-FBTFSI).

[0043] Equimolar amounts of K-FBTFSI and LiClO4 were dissolved in ultra-dry acetonitrile, and stirred for 24 hours at room temperature under nitrogen protection for ion exchange reaction. After the reaction was completed, the clear liquid was centrifuged and dried, 60 mL of acetonitrile was added, and the clear liquid was centrifuged and dried after ultrasonic dissolution. Dichloromethane was added and ultrasonicated until the solution became uniform milky white, and the solution was placed in a desiccator and allowed to stand overnight. The precipitate was centrifuged and dried in vacuo at 60°C to obtain a white solid (4-fluorobenzenesulfonyl) (trifluoromethylsulfonyl) imide lithium (Li-FBTFSI).

[0044] 2. Synthesis of MIL-88B(Fe)

[0045] Synthesis route such as Figure 2As shown, first, weigh 0.675g of ferric chloride hexahydrate (FeCl3·6H2O, 2.5mmol) and 0.166g of terephthalic acid (H2BDC, 1mmol) in a small glass bottle, add 15mL of ultra-dry N,N-dimethylacetamide (DMA), dissolve by ultrasonication and transfer to a 20mL reactor, and react at 110°C for 24h. After the reaction, cool to room temperature and centrifuge to obtain a solid product, wash with DMA and anhydrous ethanol respectively until the solution is clear, centrifuge to obtain the precipitate, and vacuum dry at 60°C. Finally, Soxhlet extraction was performed with anhydrous methanol at 100°C for 24h, vacuum dried at 60°C, and ground to obtain MIL-88B (Fe) powder. Activate by vacuum drying at 150°C for 12h before use. The structure of MIL-88B (Fe) is as follows Figure 3 shown.

[0046] 3. Preparation of MIL-88B(Fe) doped PEO-based composite solid polymer electrolyte membrane

[0047] According to EO / Li + =20:1, weigh the corresponding mass of PEO and Li-FBTFSI and dissolve them in ultra-dry acetonitrile, add MIL-88B(Fe) to the mixed solution at 5wt%, 10wt% and 15wt% of the mass of PEO, stir at 60°C and nitrogen atmosphere for 24h to obtain a uniform viscous liquid, then pour the solution into a polytetrafluoroethylene mold and place it in a dryer equipped with molecular sieves to allow most of the solvent to evaporate at room temperature. Finally, vacuum dry at 60°C for 24h, remove excess organic solvent, transfer to a glove box for cooling, and obtain MIL-88B(Fe)-doped PEO-based CPEs, which are called 5%-MIL-88B, 10%-MIL-88B and 15%-MIL-88B, respectively, and PEO without MOFs 20 -LiFBTFSI is recorded as without-MIL.

[0048] Figure 4 The results showed that MIL-88B(Fe) was successfully synthesized. Figure 5 (b), (c) and (d) show the SEM images of MIL-88B(Fe) particles. As can be seen from the figure, the MIL-88B(Fe) particles are spindles with relatively uniform and regular morphology, uniform crystal size, high crystallinity, and the particle size is mainly distributed between 150 and 500 nm. Nano-sized MIL-88B(Fe) can be evenly dispersed in the PEO matrix, thereby improving the electrochemical performance of the composite solid polymer electrolyte, improving the interface contact between the electrolyte diaphragm and the electrode, thereby reducing the interface impedance, and ultimately improving the ion migration kinetics at the interface.

[0049] Figure 6 and7 The following are photos of 5%, 10% and 15%-MIL-88B CPEs in the flat and bent states, as well as the SEM image of 10%-MIL-88B CPE. As can be seen from the figure, the CPEs prepared by MIL-88B (Fe) doping have uniform color distribution, smooth surface, good flexibility and strong processability. A small amount of particle agglomeration can be seen on the surface of the SEM image of 10%-MIL-88B CPE, and there may be some places where it is not evenly mixed, but it is relatively uniform overall. Figure 8 The EDS mapping of C, O and Fe elements on the surface of 10%-MIL-88B CPE. As can be seen from the figure, the area distribution of C, O and Fe elements is relatively uniform, further indicating that the nanofiller MIL-88B (Fe) is basically well dispersed in the polymer matrix.

[0050] Fig. 9 (a) and (b) are the CV curves of Li / without-MIL / LFP and Li / 10%-MIL-88B / LFP batteries, respectively. Both 10%-MIL-88B CPE and without-MIL SPE have obvious redox peaks, corresponding to the redox process of LiFePO4. As can be seen from the figure, compared with without-MIL SPE, the battery assembled with 10%-MIL-88B CPE has basically completely overlapped curves in 3 cycles, and the redox curves have good matching, similar areas and symmetry, and the difference between the oxidation peak and the reduction peak voltage is small, indicating that the composite solid polymer electrolyte with the addition of MIL-88B (Fe) has better electrochemical reversibility and a smaller degree of polarization during the cycle.

[0051] In order to detect the cycling stability of CPEs in the battery, Li / CPEs / LiFePO4 batteries were assembled and tested. Fig.10 The figure shows the cycling performance of Li / CPEs / LFP battery at 0.2C. As can be seen from the figure, both batteries experienced a process of increasing discharge capacity, which may be related to the structural rearrangement of the electrodes and the improvement of the contact interface between the electrolyte and the electrodes during the activation process. Among them, the first discharge capacity of the Li / without-MIL / LFP battery at 0.2C was 124.8mA·h / g, and the maximum discharge capacity reached 145.6mA·h / g in the 7th cycle, but the capacity decayed significantly after 42 cycles, which may be due to the Li +The uneven deposition of lithium dendrites pierces the separator. In comparison, the Li / 10%-MIL-88B / LFP battery exhibits higher discharge capacity and better cycle stability. Its first discharge capacity is 141.1 mA·h / g, and it reaches a maximum discharge capacity of 150.2 mA·h / g in the fourth cycle. After 100 cycles, it still has a high discharge capacity of 139.9 mA·h / g, a capacity retention rate of 99.1%, and a coulombic efficiency close to 100%.

[0052] In addition, the first discharge capacity of the Li / without-MIL / LFP battery at 0.5C is 48mA·h / g, reaching a maximum discharge capacity of 111mA·h / g at the 58th cycle, and a discharge capacity of 89.1mA·h / g after 200 cycles. In comparison, the Li / 10%-MIL-88B / LFP battery exhibits better cycle performance, with an initial discharge capacity of 106.8mA·h / g, a maximum discharge capacity of 137.5mA·h / g at the 4th cycle, and a high discharge capacity of 127.4mA·h / g after 200 cycles, and excellent cycle stability. It can be seen that the MIL-88B (Fe) filler has a positive effect on stabilizing the interface and long cycle stability.

[0053] Fig.11 and Fig.12 The rate cycle performance diagram of Li / CPEs / LFP battery and the charge and discharge curves of Li / 10%-MIL-88B / LFP battery at different rates are shown respectively. It can be seen that the Li / 10%-MIL-88B / LFP battery exhibits excellent electrochemical reversibility in the rate test, and the average discharge specific capacity at 0.1C, 0.2C, 0.3C, 0.5C, and 1C are 146.62mA·h / g, 143.42mA·h / g, 136.08mA·h / g, 122.66mA·h / g, and 98.16mA·h / g, respectively. When returning to 0.1C along the opposite path, the battery capacity is almost not lost.

[0054] However, with the increase of current density, the discharge capacity of Li / 10%-MIL-88B / LFP battery gradually decreases and the battery polarization gradually increases. This may be due to the fact that at high current density, Li + The diffusion capacity of Li is not enough to meet the electrolyte / electrode interface +The requirement of migration rate leads to increased electrode polarization and reduced discharge capacity. However, the discharge capacity of the battery assembled with 10%-MIL-88B CPE at high rate is significantly higher than that without-MIL SPE. This may be attributed to the fact that the addition of MIL-88B (Fe) can increase the contact area between the electrode and the electrolyte, inhibit the occurrence of side reactions, and promote Li + The uniform deposition on the surface of lithium metal inhibits the growth of lithium dendrites and improves the interface stability, so that it can still maintain a high charge and discharge specific capacity at high rates.

[0055] The interfacial compatibility between polymer electrolyte and lithium metal anode is an important property to ensure the safety of solid-state lithium batteries. Fig.13 and Fig.14 The AC impedance diagram and interface impedance change curve of Li / 10%-MIL-88B / Li symmetric battery at different storage times within 15 days are shown. It can be seen from the figure that the interface impedance value of 10%-MIL-88B CPE is smaller than that of without-MIL SPE prepared with PEO and Li-FBTFSI, and the interface impedance R i The value first increases and then decreases with time in the initial stage, and is basically stable after 4 days. This may be due to the scavenging effect of the porous inert filler, which removes the added trace acetonitrile solvent and other impurities, thereby reducing the interface impedance.

[0056] The interfacial stability of 10%-MIL-88B CPEs to lithium metal during lithium anode plating / stripping was investigated using Li / CPEs / Li symmetric cells. Fig.15 As shown, at 0.1 mA cm -2 At a current density of , the lithium symmetric battery using without-MIL SPE short-circuited after 235 hours of stable cycling. In comparison, the lithium symmetric battery using 10%-MIL-88B CPE was able to operate continuously and stably for 2000 hours without short circuiting, and the polarization voltage slowly decreased with the increase in cycle time. The polarization voltage increased at the beginning, which may be the result of interfacial side reactions and SEI film formation. As the cycle progresses, the polarization voltage gradually decreases, indicating that 10%-MIL-88B CPE can effectively resist the growth of lithium dendrites, and its interfacial contact will gradually improve with the continuous cycling. In addition, the uniform space charge at the electrode interface can make Li + Uniform deposition optimizes ion transport paths and hinders the growth of lithium dendrites.

[0057] The results show that CPE doped with MIL-88B(Fe) functional filler can effectively stabilize the interface between electrode and electrolyte and promote Li +Uniform deposition inhibits the growth of lithium dendrites, effectively improves the interface stability between electrolyte and lithium metal, and prolongs the service life of the battery. It can be seen that the doping of MIL-88B (Fe) helps to improve the interface compatibility between polymer electrolyte and lithium metal, effectively reduce the interface impedance, and improve the interface stability and cycle stability of the battery.

[0058] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A lithium-ion battery composite solid polymer electrolyte material, characterized in that: A new type of arylsulfonyl imide lithium salt (Li-FBTFSI) was prepared by sulfonylation and ion exchange reaction. At the same time, MIL-88B (Fe) nanoparticles were synthesized by a solvothermal method with terephthalic acid as ligand and ferric chloride hexahydrate as metal salt. Then, the MIL-88B (Fe) nanoparticles were added to the PEO matrix with the new type of arylsulfonyl imide lithium salt (Li-FBTFSI) as lithium salt to obtain a high-performance PEO-based composite solid polymer electrolyte material.

2. A method for preparing a composite solid polymer electrolyte material for a lithium ion battery, characterized in that: The following steps are involved: (1) Synthesis of novel arylsulfonyl imide lithium salt (Li-FBTFSI): 3.10 g 4-fluorobenzenesulfonyl chloride, 2.38 g trifluoromethanesulfonamide, 0.51 g 4-dimethylaminopyridine and 60 mL ultra-dry acetonitrile were added to a round-bottom flask, and 4.5 g anhydrous potassium carbonate was added after ultrasonic dissolution. The mixture was stirred at room temperature under nitrogen protection for 48 h to carry out ion exchange reaction. After the reaction is completed, the supernatant is taken by centrifugation, the solvent is removed by rotary evaporation, 30 mL of acetone is added to dissolve, the solution is dropped into 300 mL of dichloromethane, the supernatant is poured off after ultrasonication, the precipitate is taken by centrifugation, and dried at 60°C; the dried solid is dissolved in 20 mL of acetone, allowed to stand overnight, the supernatant is taken by centrifugation, the supernatant is taken by rotary evaporation, the precipitate is taken by centrifugation, recrystallized with acetone and dichloromethane, the precipitate is taken by centrifugation, dried at 60°C, and impurities are removed to obtain a white solid (4-fluorobenzenesulfonyl)(trifluoromethylsulfonyl)imide potassium (K-FBTFSI); Then, an equimolar amount of KFBTFSI and LiClO4 were dissolved in ultra-dry acetonitrile, and stirred for 24 hours at room temperature under nitrogen protection to perform an ion exchange reaction; after the reaction, the clear liquid was centrifuged and dried, 60 mL of acetonitrile was added, and the clear liquid was centrifuged and dried after ultrasonic dissolution, and dichloromethane was added and ultrasonicated until the solution became uniform milky white, and the solution was placed in a desiccator and allowed to stand overnight, and the precipitate was centrifuged and dried in vacuo at 60° C. to obtain a white solid (4-fluorobenzenesulfonyl) (trifluoromethylsulfonyl) imide lithium (Li-FBTFSI); (2) Synthesis of MIL-88B (Fe) nanoparticles: First, 0.675 g of ferric chloride hexahydrate and 0.166 g of terephthalic acid were weighed into a small glass bottle, 15 mL of ultra-dry N, N-dimethylacetamide was added, and after ultrasonic dissolution, the mixture was transferred to a 20 mL reactor and reacted at 110 °C for 24 h. After the reaction is completed, the mixture is cooled to room temperature and centrifuged to obtain a solid product, which is washed with ultra-dry N,N-dimethylacetamide and anhydrous ethanol respectively until the solution is clear, and the precipitate is centrifuged and dried in vacuum at 60°C; Finally, the product was extracted with anhydrous methanol at 100 °C for 24 h, dried under vacuum at 60 °C, and ground into powder with a size between 150 and 500 nm to obtain MIL-88B (Fe) nanoparticles; (3) Preparation of MIL-88B(Fe)-doped PEO-based composite solid polymer electrolyte membrane: According to the EO / Li + =20:1, weigh the corresponding mass of PEO and Li-FBTFSI and dissolve them in ultra-dry acetonitrile, add MIL-88B(Fe) to the mixed solution according to 10wt% of the mass of PEO, stir at 60°C in a nitrogen atmosphere for 24h to obtain a uniform viscous liquid, then pour the solution into a polytetrafluoroethylene mold, place it in a dryer equipped with molecular sieves, and allow most of the solvent to evaporate at room temperature; finally, vacuum dry at 60°C for 24h to remove excess organic solvent, transfer to a glove box for cooling, and obtain MIL-88B(Fe)-doped PEO-based CPEs.

3. Application of MIL-88B (Fe) nanoparticles in the preparation of polymer solid-state lithium-ion batteries.